Primary stability and viscoelastic displacement of mini-implant system under loading. (January 2017) - Lee, Jim; Jeong, Yong-Hoon; Pittman, Joseph; Deguchi, Toru; Johnston, William M.; Fields, Henry W.; Kim, Do-Gyoon
Abstract: Background: The objectives of the current study were to examine the effects of mini-implant diameters on 1) primary stability before bone properties are changed by active peri-implant bone remodeling and 2) the time-dependent displacement of mini-implant systems in bone under a functional radial loading and their associations with bone mineral density. Methods: Twenty one, 8 mm length mini-implants (7 each for 1.4 mm, 1.6 mm, and 2 mm diameters) were placed in mandibular sections of human cadavers (4 males and 3 females, average 69.7 (SD 13.1) years of age). Displacement of the mini-implant in wet bone was assessed during initial and subsequent continuous radial loading of 2 N in the mediolateral direction for 2 h. Mean, standard deviation and coefficient of variation of peri-implant bone mineral density were obtained using histograms of cone-beam computed tomography attenuation values. The cortical thickness along with the miniscrew site was also measured. Findings: The primary stability and displacement of mini-implants in bone were not significantly different between the 3 diameter groups ( p > 0.147, n = 21). Moderate positive correlations of time-dependent viscoelastic displacement (creep) were found with bone mineral density variability independent of the mini-implant diameters ( p > 0.11). Interpretation: The post-implantation displacements of mini-implant suggested that the orthodontic treatment loading can develop micromotion between the mini-implant and surrounding bone leading to reduction of its primary stability. Current findings also provide an insight that peri-implant bone mineral density variability plays an important role in controlling displacement of the mini-implant, which determine its stability during early and prolonged orthodontic treatment loading periods. Highlights: Mini-implants move under orthodontic treatment loading immediately after implantation. Creep likely causes micromotion between the mini-implant and surrounding bone. Primary stability and movement of the mini-implant were independent of its diameter. Variability of peri-implant bone mineral density likely relates to movement.